Maximising Olympic Distance triathlon performance: A sports physiologist's perspective - Smith, D. (Proceedings from the Gatorade International Triathlon Science II Conference, Noosa, Australia, November 7-8, 1999: Maximising Olympic Distance Triathlon Performance: A multi-disciplinary perspective, 1999)
This presentation will provide an overview of the following important physiological issues for maximising Olympic distance triathlon performance for the elite competitor: